The Influence Fashion Involvement, Price Perception, and Perceived Scarcity To Impulse Buying of Uniqlo Collaboration Products among University Students in Surabaya - Syeril Tiffany Prasetyo; Sugeng Purwanto (Manunggal Halim Jaya, 2026)
The rapid growth of the fashion industry has contributed to an increase in impulsive buying behavior, particularly for collaborative products that offer exclusivity and uniqueness. This study aims to analyze the influence of fashion involvement, price perception, and perceived scarcity on impulse buying of Uniqlo collaborative products among university students in Surabaya. A quantitative approach was employed using a survey method through questionnaires distributed to students who had purchased Uniqlo collaborative products. The data were analyzed using Partial Least Square (PLS). The results indicate that price perception and perceived scarcity have a positive and significant effect on impulse buying, while fashion involvement does not significantly affect impulse buying. The R-Square value of 0.586 demonstrates that the proposed model explains 58.6% of the variance in impulse buying behavior. These findings suggest that external factors, particularly consumers’ perceptions of price and product scarcity, play a more dominant role in stimulating impulsive purchases than individual involvement in fashion. Theoretically, this study enriches consumer behavior literature by providing empirical evidence on the applicability of the Stimulus–Organism–Response (S-O-R) framework in explaining impulse buying behavior within the context of fashion collaboration products. Practically, the findings offer valuable insights for fashion retailers, especially Uniqlo, in designing effective marketing strategies through competitive pricing and scarcity-based promotions to encourage consumer purchase intentions while understanding the purchasing behavior of young consumers.